2016
DOI: 10.1308/rcsann.2016.0159
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal compartment syndrome

Abstract: A term neonate was born with a grossly swollen and discoloured left hand and forearm. He was transferred from the local hospital to the plastic surgical unit, where a diagnosis of compartment syndrome was made and he underwent emergency forearm fasciotomies at six hours of age. Following serial debridements of necrotic tissue, he underwent split-thickness skin grafting of the resultant defects of his forearm, hand and digits. At the clinic follow-up appointment two months after the procedure, he was found to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 3 publications
0
22
0
7
Order By: Relevance
“…The most common site of occurrence is on the leg. 4 5 6 7 Late diagnosis of this complication is not uncommon and logically has worse outcomes. The consequences of this complication may be very serious; the loss of the limb is rare.…”
Section: Discussionmentioning
confidence: 99%
“…The most common site of occurrence is on the leg. 4 5 6 7 Late diagnosis of this complication is not uncommon and logically has worse outcomes. The consequences of this complication may be very serious; the loss of the limb is rare.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 Risk factors that predispose infants to a hypercoagulable state (sepsis, thrombophilic disorders, maternal diabetes) or trauma (fetal macrosomia, difficult/traumatic birth extraction, oligohydramnios, amniotic band syndrome) have been implicated, but the exact cause of NCS remains poorly understood. [2][3][4][5] The severity of NCS ranges from transient ischemia causing minimal damage to severe compartment syndrome causing growth restriction, severe contracture, loss of limb function, and limb necrosis. 5 A previous case series and literature review of NCS reported at long-term follow-up 84% of infants had persistent contracture, 82% had radiographic bony abnormalities, and 45% had persistent nerve dysfunction.…”
mentioning
confidence: 99%
“…[2][3][4][5] The severity of NCS ranges from transient ischemia causing minimal damage to severe compartment syndrome causing growth restriction, severe contracture, loss of limb function, and limb necrosis. 5 A previous case series and literature review of NCS reported at long-term follow-up 84% of infants had persistent contracture, 82% had radiographic bony abnormalities, and 45% had persistent nerve dysfunction. 2,4 Multiple publications have showed that ear-lier surgical intervention is associated with better functional outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal compartment syndrome of an extremity is a rare condition that, without prompt intervention, leads to muscular and neuronal ischemia and long-term sequelae such as Volkmann ischemic contracture and limb growth deficit 1 The etiology remains poorly understood, as do management guidelines. [2][3][4] The classical clinical presentation includes erythema, cyanosis, skin discoloration, severe swelling, blisters, hemorrhagic bullae, and desquamated necrotic skin with ulceration and eschars, up to complete gangrene of an extremity. [4][5][6][7][8] Pulses are usually detectable, but capillary refill can sometimes be diminished.…”
mentioning
confidence: 99%